ANALISIS AKTIVITAS BELAJAR SISWA BERDASARKAN GAYA BELAJAR VISUAL AUDITORIAL KINESTETIK SISWA PADA PEMBELAJARAN BIOLOGI KELAS XI IPA MAN 1 MEDAN - Siti Riska Amina; Zulkifli Simatupang (Jurnal Pelita Pendidikan, 2017)
This research aims to determine students's learning activities based on visual, auditory and kinesthetic learning styles of students XI IPA class at MAN 1 Medan Academic Year 2015/2016. The Population of this research is 60 students in two of XI IPA classes and samples were determined by using purposive sampling technique in which the sample was 18 students. The type of this research is a descriptive research. As the research instrument with 36 item of learning style’s questionnaire and the observations are done two times by using learning activities observation sheets. The survey results revealed that students with  visual learning style have the highest writing activities with a percentage of 51.1%, visual activities by 50% and motor activities with a percentage of 39.1%. Students with auditory learning style have a high listening activities with a percentage of 37.9% and oral activities with a percentage of 32.7%. Students with kinesthetic learning style have the highest oral activities with a percentage of 41.4%, and listening activities with a percentage of 39.9%.Keywords: biology learning activities, learning styles